Chapter 4 Profesjonelle fotballtreneres interaksjon med sine overordnede og assistenter - Holmemo, Jørgen (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Research on coaching in sports has long been concerned with how coaches interact with their players. In recent years, more research in sports psychology has been conducted on the coach's role. However, research on coaches' co-operation with leaders and staff in the clubs has received little attention. There is reason to argue that the way coaches handle this part of their profession can have a huge impact on how well they are able to do their job. This study explores how three experienced Norwegian elite football coaches (average 25 years of elite experience) interact with others in their clubs creating room for themselves and achieving their goals through micro-political activity and orchestration, i.e. coaches' actions to increase their own influence and power within the organization. We collected data through semi-structured interviews. Then we used content analysis based on a theoretical framework consisting of the orchestration metaphor and studies on micropolitics and the three aspects of micropolitical proficiency. The results and discussion describe how the coaches handle the negotiation process before joining a club, how they handle managers and employees, and how they have developed their micropolitical skills through their careers. Their knowledge about and attention to these processes were integral parts of their coaching and leadership challenges. Knowledge of orchestration and micropolitics seemed to be important for the coaches in the current study. We therefore provide some suggestions as to how coaches can improve their ability to handle these elements in coach education and suggest possible future research and applied implications for coaches."